Dietary Bacillus licheniformis improves the effect of Astragalus membranaceus extract on blood glucose by regulating antioxidation activity and intestinal microbiota in InR[E19]/TM2 Drosophila melanogaster. - Wang, D.; Zhang, Y.; Xu, M.; Sun, X.; Cui, X.; Wang, X.; Liu, D. (PLoS ONE, 2022)
The diabetes mellitus prevalence is rapidly increasing in most parts of the world and has become a vital health problem. Probiotic and herbal foods are valuable in the treatment of diabetes. In this study, Bacillus licheniformis (BL) and Astragalus membranaceus extract (AE) were given with food to InR[E19]/TM2 Drosophila melanogaster, and the blood glucose, antioxidation activity and intestinal microbiota were investigated. The obtained results showed that BA (BL and AE combination) supplementation markedly decreased the blood glucose concentration compared with the standard diet control group, accompanied by significantly increased enzymatic activities of catalase (CAT), decreased MDA levels and prolonged lifespan of InR[E19]/TM2 D. melanogaster. The treatments with BL, AE and BA also ameliorated intestinal microbiota equilibrium by increasing the population of Lactobacillus and significantly decreasing the abundance of Wolbachia. In addition, clearly different evolutionary clusters were found among the control, BL, AE and BA-supplemented diets, and the beneficial microbiota, Lactobacillaceae and Acetobacter, were found to be significantly increased in male flies that were fed BA. These results indicated that dietary supplementation with AE combined with BL not only decreased blood glucose but also extended the lifespan, with CAT increasing, MDA decreasing, and intestinal microbiota improving in InR[E19]/TM2 D. melanogaster. The obtained results showed that dietary supplementation with BL and AE, under the synergistic effect of BL and AE, not only prolonged the lifespan of InR[E19]/TM2 D. melanogaster, increased body weight, and improved the body's antiaging enzyme activity but also effectively improved the types and quantities of beneficial bacteria in the intestinal flora of InR[E19]/TM2 D. melanogaster to improve the characteristics of diabetes symptoms. This study provides scientific evidence for a safe and effective dietary therapeutic method for diabetes mellitus.